The mediating role of new media engagement in this digital age - Yujie, Zhang; Yasin, Megat Al Imran; Shekh Alsagoff, Syed Agil; Hoon, Ang Lay (Frontiers Media, 2022)
New Media Technologies refer to all kinds of web-related technologies like social networking sites, blogs, online social media networking, and other communication technology forms. The primary purpose of this study is to examine the mediating role of new media engagement in this digital age. Furthermore, this study defines the concept of new media, highlights the characteristics of new media technologies, and analyzes the application of new media technologies in this digital age. To meet the objectives stated, the researchers conduct a questionnaire survey to showcase that new media engagement plays a mediating role between the instructions provided to the newsroom in this digital age and the attitude of people toward social media. Results of the study state that the majority of the individuals in this digital era display positive engagement with new media technologies. People in this age believe that social media is safe and less risky for all individuals with regard to communication and interactions.